1D Nickel Coordination Polymers with an Unnatural Amino Acid Prepared by in situ Double Michael Addition of Ethylenediamine to (E, E)‐Muconic Acid. (6th November 2017) - Do, Junghwan; Kang, Jaeun; Jung, Yeonsun; Park, Yong Sun; Jacobson, Allan J.
Abstract :